2018
DOI: 10.3390/rs10040541
|View full text |Cite
|
Sign up to set email alerts
|

Fog Detection Based on Meteosat Second Generation-Spinning Enhanced Visible and InfraRed Imager High Resolution Visible Channel

Abstract: In this study, the Meteosat Second Generation (MSG)-Spinning Enhanced Visible and Infrared Imager (SEVIRI) High Resolution Visible channel (HRV) is used in synergy with the narrow band MSG-SEVIRI channels for daytime fog detection. A new algorithm, named MSG-SEVIRI SatFog, has been designed and implemented. MSG-SEVIRI SatFog provides the indication of the presence of fog in near real time and at the high spatial resolution of the HRV channel. The HRV resolution is useful for detecting small scale daytime fog t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
3
18
0
Order By: Relevance
“…It should be noted that the algorithm presented here does not differentiate between ground fog and low-level clouds. The discrimination of low-level liquid-water and higherlevel ice clouds with satellite observations is comparatively easy, especially in the Namib region (Olivier, 1995). In this study, high clouds are identified based on the brightness temperature at 10.8 µm as a proxy for cloud-top temperature, and the difference in 8.7 and 12.0 or 13.4 µm brightness temperatures is an indication of ice clouds (Strabala et al, 1994).…”
Section: Algorithm Designmentioning
confidence: 93%
“…It should be noted that the algorithm presented here does not differentiate between ground fog and low-level clouds. The discrimination of low-level liquid-water and higherlevel ice clouds with satellite observations is comparatively easy, especially in the Namib region (Olivier, 1995). In this study, high clouds are identified based on the brightness temperature at 10.8 µm as a proxy for cloud-top temperature, and the difference in 8.7 and 12.0 or 13.4 µm brightness temperatures is an indication of ice clouds (Strabala et al, 1994).…”
Section: Algorithm Designmentioning
confidence: 93%
“…A detailed overview of C-MACSP [15,41,42], RainCEIV [40], and PET [15,39] is proposed in [43]. All of the three remote sensing techniques exploit the high temporal resolution (15 min) of the MSG-SEVIRI [44] to provide a continuous monitoring of the extreme events.…”
Section: Methodsmentioning
confidence: 99%
“…From the data listed in Table 2, three datasets were derived (clear, cloudy and partially cloudy) by using cloud detection AMESIS modules for low (VIS) [31,49] and high spatial (HRV) [53] resolution. In the validation phase, we did not find features that could be related to geographic/altitude characteristics of ground-based stations.…”
Section: Resultsmentioning
confidence: 99%